Macrofungal diversity of greenhouses at the Warsaw University Botanic Garden - Szczepkowski, Andrzej; Gierczyk, Błażej; Kujawa, Anna; Dobrzyński, Piotr (Ecological Questions, 2022)
In 2019–2020 (for 13 months), 21 macrofungi species, both native (14) and inadvertently introduced from warmer regions (7), were found in greenhouses at the Warsaw University Botanic Garden. These included 13 species recorded for the first time in Polish greenhouses. Descriptions and photographs are given for 5 species identified, which are new to Poland (Gymnopus luxurians, Hemimycena ignobilis, Leucoagaricus meleagris, L. rubrotinctus, and Xylaria arbuscula s.l.). The highest variety of species was found in the greenhouses with the collection of tropical and succulents and cacti, with 11 and 8 species, respectively. The number of species ranged from five to four in other greenhouses. The current results increase the number of species reported from greenhouses in Poland to approximately 50. None of the identified species has a negative impact on the growth and health of plants in the greenhouses at the Warsaw University Botanic Garden and at present none of them are indicated as potentially invasive.